THE STRUCTURE OF A COMPOUND SENTENCE IN RUSSIAN (Conferencea, 2023)
The article reveals the means of expressing syntactic relations between parts of a complex sentence and the structure, types of compound sentences. The compositional connection that characterizes the syntactic relations of the parts of a compound sentence presupposes their equality, which is revealed only at the syntactic level. Examples of each semantics of the main issue under study are given.